Global Health Education and Advocacy: Using BMJ Case Reports to Tackle the Social Determinants of Health - Douthit, Nathan T.; Biswas, Seema (Frontiers in Public Health, 2018)
Since 2013 BMJ Case Reports (http://casereports.bmj.com/) has published over 70 global health case reports from five continents, written by doctors, nurses, students and allied health professionals. These cases, a burgeoning repository of evidence of how real patients are affected by disease, trauma, violence, sexual assault, conflict, migration, adverse living and working conditions and poor access to health care, discuss, in addition to clinicopathological findings, the global health problems affecting each patient. The global health problem analysis examines the problems of individual patients, critically appraises the literature, and describes actual and potential solutions for the patient, the local community, and patients affected by similar issues across the world. At present global health literature and learning materials lack a patient focus and real-life context in the analysis of global health problems. BMJ global health case reports are a unique and important tool to learn about and advocate for change in the social, political, cultural and financial determinants of health as they affect real patients. This growing evidence base brings together clinicians, local service providers, policy makers and government and non-governmental institutions to effect real change in patients’ lives towards improving health. Each global health case report is an excellent resource for learning, and together, these case reports provide essential reading for anyone embarking on a career in global health, and writing their own case report. The online course (http://casereports.bmj.com/site/misc/GHMA_Mar_2017.pptx) at BMJ Case Reports uses these cases and is free to access.